Editorial - Kosyan, Aram (ARAMAZD: Armenian Journal of Near Eastern Studies, 2020)
The current volume of ‘Aramazd: Armenian Journal of Near Eastern Studies’ is dedicated to the 25th anniversary of the Republic of Armenia and summarises the studies conducted in Armenia in the field of archaeology (1991-2016).